Doing the Fairy Tale Quest: Contesting the Author in the Video Game Jenny LeClue: Detectivú. Issue 2 (1st June 2022) - Harkin, Stephanie
Abstract: Despite the encouragement of women's and girls' curiosity in matriarchal and oral fairy tale traditions, their patriarchal print production in Western Europe reframed this trait as undesirable. Fairy tale print productions also troubled the tales' transformative and communal form in establishing versions that would receive ongoing duplication by attaching prominent authorial figures. In this article, I investigate the teen girl detective game as a format that reflects upon and updates these values. Taking Mografi's Jenny LeClue: Detectivú as my case study, I interpret the text as a postmodern fairy tale revision that unsettles the master narrative and the notion of the singular authorial figure. The game encourages the player's active investigatory participation while presenting a narrative that invites collaboration and a critique of the conservative author.